Cognitive Competence as a Positive Youth Development Construct: A Conceptual Review - Rachel C. F. Sun; Eadaoin K. P. Hui (The Scientific World Journal)
This paper focuses on discussing critical thinking and creative thinking as the core cognitive competence. It reviews and compares several theories of thinking, highlights the features of critical thinking and creative thinking, and delineates their interrelationships. It discusses cognitive competence as a positive youth development construct by linking its relationships with adolescent development and its contributions to adolescents' learning and wellbeing. Critical thinking and creative thinking are translated into self-regulated cognitive skills for adolescents to master and capitalize on, so as to facilitate knowledge construction, task completion, problem solving, and decision making. Ways of fostering these thinking skills, cognitive competence, and ultimately positive youth development are discussed.